Human Health Risk Assessment of Heavy Metal Concentration in Seafood Collected from Pattani Bay, Thailand - Phanwimol Tanhan; Niyada Lansubsakul; Napasorn Phaochoosak; Pattanasuda Sirinupong; Pun Yeesin; Kanjana Imsilp (Toxics, 2022)
A significant impact of marine pollution is the contamination of seafood which has raised concerns due to its potential human health risks. This current study investigated seasonal bioaccumulation of 9 heavy metals (Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, and Zn) in 14 commercially important seafood species, including 4 fish, 5 molluscs, and 5 crustacean species. Samples were collected from Pattani Bay, Pattani province, Thailand, during the dry (July 2020) and wet (February 2021) seasons. The edible samples were analyzed for heavy metal concentrations using a flame atomic absorption spectrophotometer. The bioaccumulation trend of heavy metals decreased in the sequence of molluscs > crustaceans > fish. The possible human health risks associated with heavy metal-contaminated seafood consumption were assessed. The parameters investigated for non-carcinogenic and carcinogenic were target hazard quotient (THQ), total hazard index (HI), and target cancer risk (TR). The average ranges of THQs (7.79 × 10−8–8.97 × 10−3), HIs (4.30 × 10−5–1.55 × 10−2), and TRs (2.70 × 10−9–1.34 × 10−5) were observed in the studied seafood species. The results revealed no non-carcinogenic and carcinogenic health risks from consuming these 14 kinds of seafood.